Insights on the laccase extraction and activity in ionic-liquid-based aqueous biphasic systems - Capela, Emanuel V. (2021)
Due to their catalytic properties, selectivity, and efficiency, enzymes are excellent biocatalysts. In particular, laccases are versatile multi-copper oxidases with great interest for a wide plethora of biotechnological and environmental applications. Even though several laccase-catalysed processes have been reported at an industrial level, the high costs of their downstream processing required to provide biocatalysts with high purity levels, stability and activity remains one of the main drawbacks when economically evaluating the overall processes. Aqueous biphasic systems based on ionic liquids (ILs) can be foreseen as a promising alternative approach for the extraction and activity maintenance/improvement of enzymes, essentially due to the designer solvents ability of ionic liquids. However, to take advantage of this feature and to use the full potential of IL-based aqueous biphasic systems, it is necessary to understand the effect of ILs as phase-forming constituents and how they affect the enzymes extraction and activity. In order to overcome the lack of information on this topic in the literature, in this work, IL-based aqueous biphasic systems were investigated to extract and enhance the laccase activity, in order to gather evidences that could be used to improve the enzymes downstream processing. To this end, a wide screening of imidazolium-, pyridinium-, pyrrolidinium-, piperidinium-, tetraalkylphosphonium-, and tetraalkylammonium-based ILs as phase-forming components of ABS was carried out. Furthermore, these ILs were used to create ABS combined with salts, polymers and used as adjuvants in polymer-based ABS. Most ABS comprising ILs revealed to be highly efficient extraction platforms, allowing the complete extraction of laccase for all the conditions tested, and with an enzyme activity enhancement by more than 50%. Overall, the obtained results demonstrate that laccase preferentially partitions to the most hydrophilic phase in ABS comprising ILs, both used as adjuvants or as phase-forming components, corresponding to the phase in which the IL is enriched. Furthermore, the IL chemical structure of the IL plays a significant role in the enzyme activity, where ILs with a higher number of hydroxyl groups seem to be relevant to improve the laccase activity.